The Improvement of Science Process Skills Theme 2, Subthemes 2 in Meeting 1 Through The Learning Cycle (5E) Model On The Students Grades IV-A at MI Al-Ahmad Krian Sidoarjo - Santi, Dewi Ari (Indonesian Journal of Science Learning (IJSL), 2020)
Learning Cycle (5E) model is a learning model that focuses on student-centered. In the effort of improving students’ science process skills, this study used a Learning Cycle (5E) model. The research method used in this study is classroom action research by Kurt Lewin’s model which consists of two cycles and each cycle has 4 phases. This research was conducted at MI Al-Ahmad Krian Sidoarjo in grade IV-A with 28 students as a research subject. The data were collected from interviews, documentation, observation, test, and non-test (performances and products). The research instruments were teacher and student activity sheets, interview guidelines, question items, performance assessment rubric, and product assessment rubric. Based on the results, it showed that the implementation of the Learning Cycle (5E) was carried out well which can be seen from the increasing of the thematic subject on science process skills theme 2, subthemes 2 in meeting 1 after applying the Learning Cycle (5E) model. It can be seen from the increase in the percentage of students’ learning outcomes from 75% (enough) to 100% (excellent). The result also showed the improvement of the teacher and student activity. The teachers’ activity increased from 77.9% (sufficient) in the first cycle to 91.6% (excellent) in the second cycle. Then, the students’ activity increased from 76% (sufficient) in the first cycle to 90% (excellent) in the second cycle.